Effectiveness of Melatonin Supplementation in Preventing Cognitive Decline Among Older Adults with Sleep Disorders: A Narrative Review - Bano, Sher; Mussadiq, Khizra; Ibrahim, Muhammad; Khan, Marium Nadeem; Royg, Diego Jiménez; Aun, Mohammad; Akbar, Muhammad Bilal (Indus Journal of Bioscience Research, 2025)
Melatonin, a hormone primarily secreted by the pineal gland, plays a central role in regulating circadian rhythms and sleep-wake cycles. In recent years, its potential neuroprotective properties have garnered increasing attention, particularly in the context of cognitive decline associated with aging and sleep disturbances. Older adults are disproportionately affected by both sleep disorders and neurodegenerative conditions, such as Alzheimer’s disease, where disrupted sleep contributes to accelerated cognitive deterioration. Melatonin’s antioxidant, anti-inflammatory, and mitochondrial-stabilizing effects, along with its influence on amyloid-beta clearance and synaptic plasticity, make it a promising agent in cognitive health. This narrative review explores the mechanisms through which melatonin supports neuroprotection, highlights the link between sleep disorders and cognitive decline, and evaluates clinical evidence on melatonin supplementation among older adults. Furthermore, it identifies current limitations in the research and provides future directions for clinical application and scientific inquiry. While findings are promising, further high-quality trials are essential to define melatonin’s therapeutic role in preventing cognitive impairment in aging populations. Melatonin supplementation shows promise in managing cognitive decline in older adults with sleep disorders. Its ability to regulate circadian rhythms, along with antioxidant and neuroprotective effects, supports its therapeutic potential. Melatonin not only improves sleep quality but may also help preserve cognitive function. Although limitations in existing studies—such as inconsistent dosing and short durations—warrant caution, its safety, affordability, and availability make it a compelling preventive option. Future research through large-scale, long-term studies is essential to confirm its benefits and clarify mechanisms. Melatonin may emerge as a valuable component of strategies for promoting healthy cognitive aging in the elderly.